2013
DOI: 10.1002/grl.50203
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol formation from semi‐ and intermediate‐volatility organic compounds and glyoxal: Relevance of O/C as a tracer for aqueous multiphase chemistry

Abstract: [1] The role of aqueous multiphase chemistry in the formation of secondary organic aerosol (SOA) remains difficult to quantify. We investigate it here by testing the rapid formation of moderate oxygen-to-carbon (O/C) SOA during a case study in Mexico City. A novel laboratorybased glyoxal-SOA mechanism is applied to the field data, and explains why less gas-phase glyoxal mass is observed than predicted. Furthermore, we compare an explicit gasphase chemical mechanism for SOA formation from semiand intermediate-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 46 publications
8
81
1
2
Order By: Relevance
“…These "salting-in" and "saltingout" effects are not typically accounted for when calculating partitioning and uptake coefficients for WSOGs other than glyoxal in models. 64,65 Recent field evidence suggests that isoprene−SOA is directly modulated by an abundance of sulfate in the southeastern U.S. 66 Sulfate-induced molality impacts on partitioning and uptake of isoprene oxidation products, 27,67 the subsequent rate of their multiphase reactions, 46,48 partitioning of reaction products, or a combination of these effects is consistent with these field observations. However, the dominant reason(s) for the strong associations between sulfate and this significant portion of ambient SOA remains elusive.…”
Section: ■ Introductionsupporting
confidence: 58%
“…These "salting-in" and "saltingout" effects are not typically accounted for when calculating partitioning and uptake coefficients for WSOGs other than glyoxal in models. 64,65 Recent field evidence suggests that isoprene−SOA is directly modulated by an abundance of sulfate in the southeastern U.S. 66 Sulfate-induced molality impacts on partitioning and uptake of isoprene oxidation products, 27,67 the subsequent rate of their multiphase reactions, 46,48 partitioning of reaction products, or a combination of these effects is consistent with these field observations. However, the dominant reason(s) for the strong associations between sulfate and this significant portion of ambient SOA remains elusive.…”
Section: ■ Introductionsupporting
confidence: 58%
“…A recent data analysis study using GAMMA (Sumner et al, 2014) suggested a possible role for photo-enhanced chemistry in aaSOA formation by glyoxal involving organic photosensitizers such as fulvic acid (Monge et al, 2012). This chemistry can be represented in simpleGAMMA by including irreversible glyoxal uptake with γ ∼ 10 −3 during sunlit hours, consistent with Fu et al (2008), who based their representation on the experiments of Liggio et al (2005), and with Waxman et al (2013). A reactive uptake formulation was also used by Pye et al (2013) to represent aaSOA formation by IEPOX.…”
Section: Discussion and Outlookmentioning
confidence: 93%
“…Glyoxal forms SOA with higher yields during the day than at night due to OH aqueousphase chemistry (Tan et al, 2009;Volkamer et al, 2009;Sumner et al, 2014). We use a daytime γ of 2.9 × 10 −3 for glyoxal from Liggio et al (2005) and a nighttime γ of 5 × 10 −6 (Waxman et al, 2013;Sumner et al, 2014). The SOA yield of methylglyoxal is small compared with that of glyoxal (McNeill et al, 2012).…”
Section: Chemical Mechanism For Isoprene Soa Formationmentioning
confidence: 99%